THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS AND WORKING ENVIRONMENT ON EMPLOYEES’ PERFORMANCE OF EXIM DEPARTMENT AT PT APPAREL ONE INDONESIA 2 - Atika - Rahmadhiyati; Fatchun - Hasyim; Subandi - Subandi (Politeknik Negeri Semarang, 2019)
This research aims to analyze the influence of individual characteristics and working environment on employees’ performance of exim department at PT Apparel One Indonesia 2. Questionnaire was used as an instrument of primary data collection which was distributed to 30 respondents. This research employed a multiple regression analysis method. The calculation results of the method determined that the individual characteristics partially has a positive and significant influence on employees’ performance however the working environment has no significant influence on employees’ performance. The individual characteristics and working environment simultaneously influenced employees’ performance with the contribution of 61.9%, while the remaining 38.1% are influenced by other factors which are not included in this study